Determinants of acute respiratory infection among children under-five years of age in the Philippines - Rodriguez, Ma. Victoria C. (Quezon City Population Institute, University of the Philippines Diliman, 2008)
This study used the logistic regression model with the 2003 National Demographic and Health Survey to determine the factors that affect acute respiratory infection(ARI) among Filipino children below five years old. The study cases are examined in three groups.: (1) children 0 to 59 months old, (2) 6 to 59 months old, and (3) 12 to 59 months old because there are some independent variables that are applicable only to sub groups. The present study did not provide support to the Mosley and Chen framework on child survival which argues that socioeconomic variables operate through the proximate determinants to affect child survival,. With ARI prevalence as measure of child morbidity, the effects of socioeconomic variables is direct and do not operate through proximate factors but none of which turned significant. Among the socioeconomic variables examined, mother's education, socioeconomic status and region emerged significant. While the effect of region is direct, maternal education interacts with socioeconomic status in affecting ARI prevalence. All other things being equal, children in the Visayas are three times (3X) more likely to contract ARI, while those in other Luzon and Mindanao are twice as likely to suffer from ARI compared to those in the National Capital(NCR) region for all age groups. Even if the mother belongs to the two poorest and fourth categories of socioeconomic status but she has high school education, her children 0-59 months old are less likely to experience ARI. Moreover, even if the mother has elementary or lower education but does not not belong to the poorest and belongs to either the second and fourth categories of the socioeconomic scale, her children of the same age are less likely to suffer from ARI. With children 12-59 months old, the effect of socioeconomic status additive, that is, the higher the socioeconomic status, the lower the chances of having ARI. Maternal education did not emerge significant. Age of child consistently emerged as an important demographic control in analyzing the determinants of ARI, regardless of the type of sample studied.
""
Thesis
Keywords: Respiratory infection in children -- Philippines -- Barangays; Demographic surveys -- Philippines -- Barangays; Health surveys -- Philippines -- Barangays; Child health services